Compression of Brachial Vein between Two Lateral Roots of Median Nerve - A Case Report - Ameet KJ,; Mamatha T,; Rajalakshmi R,; Vasudha VS, (Faculty of Medicine, UKM Medical Centre, 2015)
During gross anatomy dissection, variation in the formation of median nerve of the upper limb was discovered in the right upper extremity of a 57-year-old male cadaver. Three roots contributed to the formation of median nerve instead of usual two roots i.e. two lateral roots and one medial root. After being formed the median nerve descended medial to the axillary artery. Between the two lateral roots brachial vein passed to open into the axillary vein. Anatomical variations in the formation of nerves and their unusual relationship to the surrounding structures can be the cause of nerve compression syndromes and vascular problems.